Dental professionals' role in the fight against COVID-19: current evidence - Crowder, Lauren (Evid Based Dent, 2021)
Data sources Five databases were used to search for articles: PubMed, Embase, Scopus, Web of Science and Cochrane. Study selection All articles with the relevant topics related to COVID-19 and limited to Italian and English Language (with available English abstract) were screened. Additionally, included articles were screened for relevant references. Date extraction and synthesis Two of the authors reviewed the titles and abstracts obtained from the search and screened for relevance. Databases were searched from January 2020 to the end of April 2020. Exclusion and inclusion criteria were detailed. No specific study type or design was mentioned. Results The overview covered the transmission pathway of COVID-19 in the dental setting. It detailed the protective mechanisms to reduce infection and transmission: airway protection; eye protection; triaging; antimicrobial agents; hand hygiene; reducing aerosol generation; and strict disinfection. Conclusion The overview supplied specific information for dental professionals, on both protection from COVID-19 and prevention of transmission of the virus. While a useful overview, with practical implications and advice for professionals, there is more emerging evidence post-publication as we learn more about the virus.